Uso de diferentes herbicidas no controle de Myriophyllum aquaticum - Negrisoli, E. [UNESP] (2003)
This work was carried out at the Advanced Weed Research Nucleus - UNESP, Botucatu-SP, to evaluate the control of Myriophyllum aquaticum by applying different herbicides in post emergence. The herbicides and doses (g ha-1) tested were: diquat (Reward) at 204 g a.i. ha-1, diquat at 102 and 204 g a.i. ha-1 + agral at 0.1% v/v; 2,4-D (DMA 806 BR) at 1,340, 670, 335 and 167 g a.e. ha-1; glyphosate (Rodeo) at 3.360 g a.e. ha-1 + Aterbane at 0.5% v/v and imazapyr (Arsenal) at 250 g a.e. ha-1. Small tanks (60 x 60 x 45 cm) with about 120 L water capacity, plus 20 L of soil were used. The plants were counted (20 stems), and distributed in the plots. Plant phytotoxicity was evaluated at 2, 6, 9, 11, 13, 17, 20, 23, 26, 30 and 36 days after application (DAA). Herbicide spraying was performed with a backpack sprayer, using a 2.0 bar for CO2 pressure, consuming 180 l ha-1 volume and 110.02 VS fan type nozzles. The herbicide diquat showed the first symptoms of intoxication at 2 DAA, and regardless of the dose applied, provided overall control of Myriophyllum plants at 20 DAA, with plant regrowth being observed at 23 DAA. The 2,4 D herbicide provided 100% control at 23 DAA, for doses 1,340 and 670 g ha-1. However, for the other doses tested (335 and 167 g ha-1), the control was not effective. The herbicides glyphosate and imazapyr were not efficient in controlling this plant.